Stability Assessment of the Excavated Rock Slope at the Dagangshan Hydropower Station in China Based on Microseismic Monitoring - K. Ma; N. W. Xu; Z. Z. Liang (Advances in Civil Engineering)
A high-resolution microseismic (MS) monitoring system was implemented at the right bank slope of the Dagangshan hydropower station in May 2010 to analyse the slope stability subjected to continuous excavation. The MS monitoring system could real-time capture a large number of seismic events occurring inside the rock slope. The identification and delineation of rock mass damage subject to excavation and consolidation grouting can be conducted based on the analysis of tempospatial distribution of MS events. However, how to qualitatively evaluate the stability of the rock slope by utilizing these MS data remains challenging. A damage model based on MS data was proposed to analyse the rock mass damage, and a 3D finite element method model of the rock slope was also established. The deteriorated mechanical parameters of rock mass were determined according to the model elements considering the effect of MS damage. With this method, we can explore the effect of MS activities, which are caused by rock mass damage subjected to excavation and strength degradation to the dynamic instability of the slope. When the MS damage effect was taken into account, the safety factor of the rock slope was reduced by 0.18 compared to the original rock slope model without considering the effect. The simulated results show that MS activities, which are subjected to excavation unloading, have only a limited effect on the stability of the right bank slope. The proposed method is proven to be a better approach for the dynamical assessment of rock slope stability and will provide valuable references for other similar rock slopes.